PENINGKATAN PRESTASI AKADEMIK DENGAN PEMBINAAN SOFTSKILL GURU MI AL-ISLAM, GROBAGAN, SURAKARTA - Abdullah, Yusuf; Giyoto (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
AbstractBackground of the Problem: The research focuses on the management process of guiding teacher soft skills through halaqoh activities for improved academic achievement succession at MI Al-Islam, Grobagan, Surakarta. This sets the context and highlights the significance of investigating the topic. Research Objectives:The objectives of the study are to describe the management process involved in guiding teacher soft skills through halaqoh activities and to identify the benefits derived from this guidance for teachers and students. This section outlines the specific goals of the research. Methodology: The research methodology employed a qualitative approach. The study gathered data through observation, interviews, and document analysis. The participants included principals, musyrifs, mu'allims, and teachers involved in halaqoh activities. This section provides an overview of the research methodology and data collection methods used. Conclusion: The study yielded four significant findings. Firstly, the planning phase involved formulating objectives, establishing standardization, preparing agendas, and creating SOPs. Secondly, the organizing phase assigned tasks to principals, musyrifs, and mu'allims. Thirdly, the implementation of halaqoh activities resulted in improved worship quality, controlled Quran recitation, and enhanced teacher soft skills. Lastly, control measures were carried out by the principal and mu'allims. This section summarizes the key findings obtained from the research. Keywords: academic, achievement, teacher, soft skills, halaqoh